Predicting Migrants and Refugees in the African Continent: A Case Study of the Horn of Africa and Sub-Saharan Africa - Al-Taib Omar Ahmed Mohammed; Duaa Jamal Al-Din Zain Al-Abidin (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
The study aimed to predict the numbers of migrants / displaced persons and refugees in the Horn of Africa and sub-Saharan, accordance to the statistical model describes - diagnose and predicting the migrants in the years 2015 up to 2050, And to know the effects of migration and displacement as well as the reasons that led to the migration and displacement of the large quantity of that area and the work necessary to reduce these phenomena, where the study of this area because it is one of the most migratory areas of the population due to several reasons including the lack of the most basic elements of life to live as a decent life - wars and political and tribal conflicts - poverty, ignorance, backwardness and illiteracy, food insecurity, The study found that Egypt, Ethiopia, Eritrea and the Sudan all participated in all types of migration, refugees, naturalization or asylum, and the most countries in terms of refugees in the region is Somalia. The study recommended limiting migration, providing necessary services and combating illegal migration to reduce risks such as trafficking in evil, loss and death as a result of drowning.